2018
DOI: 10.14419/ijet.v7i4.33.23568
|View full text |Cite
|
Sign up to set email alerts
|

Semiotics at Discursive Texts and Images in Online News

Abstract: The paper established an inappropriate relationship of text and image that should interact in one whole package of online news. It applied Semiotics analysis to go under the problems occurred. The analysis was developed to respond the question: why should be the text and image in online news associated? Do they match? Developed in three levels of analysis processes-analysis of relevant engagement in text and image; extended analysis of discursive relationship involved in news that turned to hoax; the intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Information value is prioritized, but aesthetics and layout policies also factor into photo selection. Another study (Heryono & Faisal, 2018) employed semiotics analysis to understand the relationship between text and image in news trying to answer the question of why the text and image in online news should be associated and if they match. It analyzed three levels of analysis processes, including the engagement in text and image, the discursive relationship involved in the news that turned into a hoax, and the intention of attaching the misplaced image to the text.…”
Section: Research Importancementioning
confidence: 99%
“…Information value is prioritized, but aesthetics and layout policies also factor into photo selection. Another study (Heryono & Faisal, 2018) employed semiotics analysis to understand the relationship between text and image in news trying to answer the question of why the text and image in online news should be associated and if they match. It analyzed three levels of analysis processes, including the engagement in text and image, the discursive relationship involved in the news that turned into a hoax, and the intention of attaching the misplaced image to the text.…”
Section: Research Importancementioning
confidence: 99%
“…Heryono and Helmy note that the verbal or textual expression of ‘words’ is not the only way to signify hate [ 75 : 241]. Graphic images, metaphors, or symbolic objects such as flags or national monuments can be nonverbal signs of hate [ 142 : 446–447, 45 : 309–332, 11 : 193–196, 118 : 33–41].…”
Section: The Semiotics Of Hate Speech the South African Legislative A...mentioning
confidence: 99%
“…It has been suggested that racialised speech is the most prevalent form of hate speech on social media platforms [ 130 : 89]. However, it is not just the verbal or textual expression of ‘words’ that can denote hate [ 75 : 241]. Graphic images in the form of pictures and metaphors, or objects such as flags can also be considered hate speech [ 142 : 446–447, 45 : 309–332].…”
Section: Introductionmentioning
confidence: 99%